2020
DOI: 10.1002/cam4.3325
|View full text |Cite
|
Sign up to set email alerts
|

Virome assembly and annotation in brain tissue based on next‐generation sequencing

Abstract: The glioblastoma multiforme (GBM) is one of the deadliest tumors. It has been speculated that virus plays a role in GBM but the evidences are controversy. Published researches are mainly limited to studies on the presence of human cytomegalovirus (HCMV) in GBM. No comprehensive assessment of the brain virome, the collection of viral material in the brain, based on recently sequenced data has been performed. Here, we characterized the virome from 111 GBM samples and 57 normal brain samples from eight projects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…Taking all of the controversies into account, a recent systematic review of 81 studies recruiting 7024 GB samples and 2420 blood samples revealed that HCMV is expressed in 36% and 45.2% of samples, respectively ( 108 ). Importantly, none of the healthy surrounding brain tissues employed as a control counterpart were detected to express HCMV genes or their products, indicating a high level of protection against off-tumor cytotoxicity for potential CMV-based immunotherapeutics for GB patients ( 72 , 109 112 ).…”
Section: Expression Of Hcmv In Gbmentioning
confidence: 99%
“…Taking all of the controversies into account, a recent systematic review of 81 studies recruiting 7024 GB samples and 2420 blood samples revealed that HCMV is expressed in 36% and 45.2% of samples, respectively ( 108 ). Importantly, none of the healthy surrounding brain tissues employed as a control counterpart were detected to express HCMV genes or their products, indicating a high level of protection against off-tumor cytotoxicity for potential CMV-based immunotherapeutics for GB patients ( 72 , 109 112 ).…”
Section: Expression Of Hcmv In Gbmentioning
confidence: 99%
“…In 7 studies, NGS was used to detect the HCMV in 681 tumors. DNA was sequenced in two of these studies [71,94]; RNA was sequenced in four [77,91,93,97]; and one was a metagenomic analysis [72]. None of these studies found evidence of HCMV nucleic acids (Table 7).…”
Section: Detection Of the Hcmv Genome By Next-generation Sequencingmentioning
confidence: 99%
“…ISH was used in 15 studies of 339 tumor samples that included 18 analyses[2,36,44,50,52,54,56,61,63,66,76,78,87,95,96]. NGS was conducted in 681 tumor samples in 7 studies[71,72,77,91,93,94,97].…”
mentioning
confidence: 99%
“…Recently, researchers aimed to detect CMV in 36 infantile brain tumors other than glioblastoma multiforme, and viral DNA was not detected in any of these tumors [ 27 ]. Furthermore, comprehensive assessment of the brain virome in 111 GBM tumors revealed the absence of CMV [ 28 ]. It was stated that the reason for the conflicting findings lies in the lack of sensitivity in the methods used by the different research groups.…”
Section: Herpesviruses As Potent Causative Agents In Brain Tumorsmentioning
confidence: 99%